Comparative study of diversity of different-aged sessile oak stands in the Börzsöny Mountains - Trenyik, Petra; Borcsa-Bodolay, János; Molnár, Marianna; Barczi, Attila; Czóbel, Szilárd (JOURNAL OF LANDSCAPE ECOLOGY, 2013)
Coenological based diversity examinations were carried out in the Börzsöny offset on the sessile oak dominated stands. Börzsöny is one of our most reprieved mountain with low human impact. It has been a part of the Danube-Ipoly National Park since 1997, and it is a part of the Natura 2000 network too. In spite of the present sylviculture it is covered in natural forests which are very rich in different species. For the forestries, it is the sessile oak that is one of the most preferred native tree species so we chose our examination substances based on this fact. To reveal the sylviculture’s effects on the biodiversity, as a first step botanical survey of selected sampling plots were carried out in 6 forest stands, characterised by same standard parameters, but representing different age groups, in order to find out their structural and dominancial relations. The Shannon- and Simpsondiversity indices were used for comparison of biodiversity values of different age-groups. Altogether 88 vascular plant species (15 trees, 11 shrubs, 62 herbaceous taxa) were identified in the stands of sessile oak woodlands. Only two invasive taxa, the Robinia pseudo-acacia and the Solidago canadensis, appeared with low covers on the records.The diversity of the canopy level was the highest at the 19-year-old stand, and the lowest at the oldest, 92-yearoldstand. The diversity of the shrub layer was the highest at the 61-year-old and lowest at the 2-year-old stand.In case of the ground level increasing diversity values were noticed between the 2 and 61 years old groups, thenthe diversity values decreased at the stands which are older than 61.
Keywords: diversity; forest; sessile oak woodlands; Börzsöny Mountains